2014
DOI: 10.5037/jomr.2014.5203
|View full text |Cite
|
Sign up to set email alerts
|

A Reliable and Valid Survey to Predict a Patient’s Gagging Intensity

Abstract: Objectives: The aim of this study was to devise a reliable and valid survey to predict the intensity of someone's gag reflex. Material and Methods: A 10-question Predictive Gagging Survey was created, refined, and tested on 59 undergraduate participants. The questions focused on risk factors and experiences that would indicate the presence and strength of someone's gag reflex. Reliability was assessed by administering the survey to a group of 17 participants twice, with 3 weeks separating the two administratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…A number of questionnaires to assess the gag reflex have been presented and revised . Although these questionnaires can identify patients with a gag reflex, they do not provide quantitative information about sensitivity to specific dental procedures.…”
Section: Discussionmentioning
confidence: 99%
“…A number of questionnaires to assess the gag reflex have been presented and revised . Although these questionnaires can identify patients with a gag reflex, they do not provide quantitative information about sensitivity to specific dental procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Once consented, patients completed the PGS (scored 0-13) (Figure 1). 4 Next, 3 measured sprays of premixed topical 2% lidocaine and phenylephrine 0.25% were instilled in each nostril, as is standard practice in this clinic. FL-S was initiated between 2 and 15 minutes after spray was instilled.…”
Section: Methodsmentioning
confidence: 99%
“…To our knowledge, gag has not been a focus of study in association with FL-S, though gag has received attention in relation to dental procedures. [2][3][4][5] Several studies have evaluated discomfort of FL without stroboscopy, and have found it to be better tolerated than rigid laryngoscopy. [6][7][8][9][10] One approach to reduce discomfort during FL has been to use topical anesthetics and vasoconstrictors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Holding the dental mirror: "mild gagging" (G2), "moderate gagging" (G3), "severe gagging" (G4) and "very severe gagging "(G5), during intraoral examination before treatment (Figure 2). A year later, the Predictive Gagging Survey (PGS) questionnaire was developed to predict someone's tension to gag (Hearing et al, 2014). It is a single-page questionnaire (10 questions) investigating potential risk factors of gagging, through different experiences and behaviours.…”
Section: Instructionmentioning
confidence: 99%